Production, purification and characterization of a new chitosanase enzyme and improvement of chitosan pentamer and hexamer yield in an enzyme membrane reactor. (August 2014) - Sinha, Sujata; Chand, Subhash; Tripathi, Pushplata
Abstract An extracellular endochitosanase was purified and characterized from the culture supernatant of Streptomyces zaomyceticus C6, isolated from garden soil. It was a constitutive chitosanase producer, producing chitosanase in the culture medium even without chitosan as an inducer. The chitosanase was further purified to homogeneity by acetone fractionation followed by column chromatography. The molecular weight of chitosanase was found to be 95 kDa, using SDS-PAGE and gel filtration chromatography. The maximum velocity of chitosanase was attained at 60°C when the pH was maintained at 5.5. The enzyme was stable over a temperature range of 0–50°C and a pH range of 4.5–6.5, and about 20% of the initial activity was retained even after heating at 90°C for 10 min. The isoelectric point of the enzyme was found to be 6.5. Chitosanase showed wide substrate specificity towards chitosan substrates, but was not able to degrade chitin. An enzyme membrane reactor equipped with an ultra filtration membrane having a cut-off of 3000 Da was used for the fractionation of chitosan oligosaccharides produced by the purified chitosanase enzyme and an improved yield of chitosan pentamer (0.1 mg/ml) and hexamer (0.6 mg/ml) was achieved.